Comparison of Concrete and Asphalt Pavements: Cost and Time Analysis on The Bendung-Bantengan Road Section In Mojokerto District - Rizky Haris, Ahmad; Oetomo, Wateno; Marleno, Risma (Pelopor Publikasi Akademika, 2025)
Road infrastructure development plays a crucial role in supporting connectivity, mobility, and economic growth. This study analyzes and compares the cost and time aspects of concrete and asphalt pavement construction on the Bendung-Bantengan road segment in Mojokerto Regency. The methods applied include an analysis of average daily traffic (ADT) data, soil California Bearing Ratio (CBR) tests, and regional topography assessments. The asphalt pavement design adheres to the 2017 Manual for Pavement Design (MDPJ), while the concrete pavement design follows the Pd T-14-2003 guidelines. The findings reveal that concrete pavement with a thickness of 25 cm incurs a total cost of IDR 2.49 billion, which is more economical in the long term compared to asphalt pavement costing IDR 3.36 billion. In terms of construction time, concrete pavement requires a shorter duration of 108 days, whereas asphalt pavement takes 120 days to complete. Concrete pavement also demonstrates superior durability and resistance to heavy traffic loads, making it an ideal choice for areas with high traffic intensity and stable soil conditions. Conversely, asphalt pavement, despite its lower initial cost and faster implementation, demands more frequent maintenance, resulting in higher long-term expenses. This study underscores the importance of selecting the appropriate pavement type based on traffic conditions, budget constraints, and project timelines. The findings contribute to more efficient and sustainable road infrastructure planning, offering valuable insights for policymakers and engineers tasked with improving regional connectivity and infrastructure resilience.